Modern control technology: components and systems (photo) - T. Kilian Christopher (Delmar Thomson Learning, 2000)
Modern Control Technology: Components and Systems, 2nd Edition provides an introduction to automatic control systems and components that is both comprehensive and up-to-date. Logically organized, this book takes the reader on a journey through a control system. Each chapter examines a different functional part, z.